Gene Duplication Accelerates the Pace of Protein Gain and Loss from Plant Organelles. (21st November 2019) - Costello, Rona; Emms, David M; Kelly, Steven
Abstract: Organelle biogenesis and function is dependent on the concerted action of both organellar-encoded (if present) and nuclear-encoded proteins. Differences between homologous organelles across the Plant Kingdom arise, in part, as a result of differences in the cohort of nuclear-encoded proteins that are targeted to them. However, neither the rate at which differences in protein targeting accumulate nor the evolutionary consequences of these changes are known. Using phylogenomic approaches coupled to ancestral state estimation, we show that the plant organellar proteome has diversified in proportion with molecular sequence evolution such that the proteomes of plant chloroplasts and mitochondria lose or gain on average 3.6 proteins per million years. We further demonstrate that changes in organellar protein targeting are associated with an increase in the rate of molecular sequence evolution and that such changes predominantly occur in genes with regulatory rather than metabolic functions. Finally, we show that gain and loss of protein target signals occurs at a higher rate following gene duplication, revealing that gene and genome duplication are a key facilitator of plant organelle evolution.